The right to equality and the position of the constitutional judiciary - عمر, شورش حسن; عبد الله, خاموش عمر (Journal of Legal Sciences, 2017)
The public rights and freedoms are important constitutional issues; hence, all countries confirm them within the constitutional and legal texts. The principle of equality is considered one of the fundamental principles of the public rights and freedoms; therefore, all authorities must sponsor equality and maintain it, even though it is difficult to achieve equality in absolute terms among all individuals. The constitutional courts use various concepts that affect their rulings, based on their interpretation and determination of the concept of the principle of equality, because there are several understandings of the “principle of equality”. A careful reading of the judicial decisions reveals different meanings to the concept of the equality principle implemented in the rulings of the constitutional tribunals. The increasing role played by the courts in control over the constitutionality of laws and the discretionary power given to the constitutional judge, sometimes lead to overlooking the principle of equality. This paper presents the determination of the concept of “equality principle” as it relates to comparative constitutional jurisdiction, and elaborates on how the constitutional judge addresses such principle; within the context of three topics.The title of the first topic is “The Constitutional Value of the Equality Principle”, and focuses on studying the following three points: the concept of the “equality principle”, its sub principles, and its constitutional value. The title of the second topic is “The Equality Principle and the Discretional Authority of the Constitutional Judge”, and this topic discusses the following three points: the equality principle and attainment of the public interest, interpretation of equality principle among distinctive legal centers, and the influence of political obstacles on equality principle. Lastly, the discussion focuses on the legitimate objectives of breaching the principle of equality, through the following points: breach as a result of legislative correction, breach that comes from positive discrimination, and the legitimate breach that results from the division of electoral districts.